Cholesterol lowering your risk (Santa Monica : Pyramid Film & Video, 1989)
The video presents viewers with straightforward and practical method for lowering their own serum cholesterol level. It's also includes recommendations on diet, exercise and medication
Keywords: Food -- Cholesterol content; Cholesterol; Low -- cholesterol diet